DAMPAK PABRIK SRITEX TERHADAP KUALITAS PERMUKIMAN PADA WILAYAH SEKITAR PABRIK - Ardhina Kusuma Wardani; Kuswanto Nurhadi; Isti Andini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
Sritex plant keeps growing which is resulting directly or indirectly attracts many labor to reside Sritex plant’s neighbourhood in order to facilitate their activities. Whereas, the Permenperin (Industrial Minister’s Regulation) No. 35 of 2010 states that the minimal distance of house to the location of plant should be more than 2000 meters recalling the hazard potentially generated by the plant to the living of the society staying there. The arrival of the labor from outside Sukoharjo Districts and surrounding areas who reside Sritex plant’s neighbourhood cause environmental burden increasing. On the other side, residents who oriented economic and can take advantage of the opportunities, their economic conditions improved and standard life increased by the existence of the Sritex plant. Based on these problems, this research want to know how impacts the existence of Sritex plant against settlement quality at Sritex plant’s neighbourhood. This research uses quantitative methods supported by several analysis techniques, including descriptive narrative analysis to identify the characteristics of Sritex plant and Paired Sample T-Test analysis to identify settlement quality at Sritex plant’s neighbourhood. The characteristic of Sritex plant divided into expanding and not expanding. While settlement quality is divided into a significant change and insignificant change / stagnant. Then an analysis of the impact of Sritex plant against settlement quality at plant’s neighbourhood using an explanatory descriptive analysis from the results of the previous analysis. Based on the results of the analysis known that the impact of Sritex plant against settlement quality viewed from the physical character of nature (Nature), social community (Society), residential buildings (Shells) and network system (Network) in the entire research area, from 17 sub variables, there are 12 sub variables changed or equal to 71% of settlements quality changed due to the expanding of Sritex plant. So known to occur relations, in which Sritex plant that expands impact on the changing significant of settlement quality on research area which is 2.000 meters of Sritex plant. The impact of expanding Sritex plant against variable of settlement quality from largest to smallest is the first Nature and Society variable, the second Network variable and the third Shell variable. Keywords:the impact of plant, quality settlement